A STUDY ON AWARENESS OF TAXATION AMONG GENERAL PUBLIC - Nisha.S, Mrs.Aruna A.R (International Journal of Advanced Science and Technology, 2020)
Tax is an obligatory liability for every citizen of the country. This paper attempted to understand the level of awareness of taxation procedure, source of awareness of the taxation and opinion in e-filing procedure of tax among the general public with special reference to Chennai region. It was found in the study that there is high level of awareness of taxation procedure, Internet is the major contributor for taxation information and lower and middle income groups are not highly comfortable with e-filing procedure. The research method followed is descriptive research. The data is collected through a questionnaire and the sample size is 1718. Convenience sampling method is adopted in the study to collect the data. The samples were collected from the general public with special reference to Chennai region. The independent variables are gender, income level and education level of respondents. The dependent variables are level of awareness of taxation procedure, source of awareness of the taxation and opinion in e-filing procedure of tax. The researcher used graphs to analyze the data collected.